1995
DOI: 10.1063/1.359366
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the characteristic dimensions for porous sound-absorbing materials

Abstract: The concept of characteristic thermal dimension was recently introduced to predict the behavior at high frequencies of the bulk modulus of fluids saturating a porous frame. This thermal dimension is closely related to the specific surface of the solid porous frame. It is shown that the standard Brunauer, Emmett, and Teller method (BET) of measuring the specific surface and acoustical measurement of the bulk modulus are in good agreement, and that the viscous dimension can be evaluated unambiguously from the BE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…These macroscopic parameters are of utmost importance to characterize the thermal dissipation mechanisms in sound absorbing materials. 1,10,31 Finally, the PUC approach is presented here as a simple microstructural method that could be used to extract other macroscopic and dynamic acoustical properties from a porous medium, such as the dynamic thermal and viscous permeabilities, directly computed on a three-dimensional reconstructed idealized PUC. 32 FIG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These macroscopic parameters are of utmost importance to characterize the thermal dissipation mechanisms in sound absorbing materials. 1,10,31 Finally, the PUC approach is presented here as a simple microstructural method that could be used to extract other macroscopic and dynamic acoustical properties from a porous medium, such as the dynamic thermal and viscous permeabilities, directly computed on a three-dimensional reconstructed idealized PUC. 32 FIG.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth mentioning that the studied thermal characteristic lengthcommonly used in acoustics of porous media-is a parameter closely related to the specific surface of the solid porous frame. 10 This article is organized as follows. Section II describes the studied porous media, the experimental setup, and the method of idealized PUC reconstruction.…”
Section: Introductionmentioning
confidence: 99%
“…Champoux and Allard 22 and Henry et al 23 reported a slightly different expression for the polytropic exponent n.…”
Section: ͑A6͒mentioning
confidence: 99%
“…͑4͒ shall be solved by using the proper boundary condition on the fibers. In the literature [1][2][3][4][5][6][7][8][9][10][11][12] one assumes that the temperature rise on the fibers is zero. But this is not accurate for light commercial glass wool, because the heat capacity of the glass fibers per volume is not infinitely great compared to the heat capacity of the air.…”
Section: General Theorymentioning
confidence: 99%
“…The established way of predicting the acoustical properties of fiber materials is by use of the theory of porous materials, which has been described by many authors. [1][2][3][4][5][6][7][8][9][10][11][12] In this theory, one assumes that the material consists of a matrix with circular pores of small radius. The compressibility of the air in the pores can be computed if one knows the radius of the pores, but for fibrous material it is not obvious how one finds the radius of the pores from the diameters of the fibers and their mean distances.…”
Section: Introductionmentioning
confidence: 99%